Analysis of hearing outcome following canal wall up and canal wall down mastoidectomy in squamosal type of chronic suppurative otitis media: A comparative study - Samanta, Mainak; Gayen, Ganesh Chandra; Ray, Ritam (Asian Journal of Medical Sciences, 2023)
Background: Chronic suppurative otitis media (CSOM) is a major health issue in developing countries causing persistent problem and may lead to life-threatening complications. This major health issue and its complications can be best avoided by early and effective treatment. Aims and Objectives: The aim is to compare the outcome in terms of hearing improvement following canal wall up and canal wall down mastoid surgery. Materials and Methods: This prospective study was conducted in Otorhinolaryngology Department of a Burdwan Medical College and Hospital, Burdwan, a tertiary care hospital in Burdwan from April 2019 to August 2020 and 50 clinically diagnosed cases of COM (Squamous type) were included in this study after through history taking and meticulous clinical examination. Patients were divided in two Groups (Group-A and Group-B) with 25 patients in each group randomly and Group-A patients undergone canal wall up mastoidectomy and Group-B patients undergone canal wall down mastoidectomy (CWDM). Now, before performing surgery, a pre-operative pure tone audiometry was performed for each of the patients and a follow-up pure tone audiometry was done again, 2-month post-operative period. These results were compared to assess the degree of hearing improvement in the two different operative procedures, namely, canal wall up and CWDM. Results: In Group-A, the mean hearing gain (mean±SD) of patients was 12.5700±0.9856. In Group-B, the mean hearing gain (mean±SD) of patients was 8.4200±5.0051. Difference of mean hearing gain with both groups was statistically significant (P=0.0002). Chi-square value: 0.1678; P=0.9195. Conclusion: Hearing gain was more with canal wall up compared to CWDM in CSOM which was statistically significant.